Social buffering in a eusocial invertebrate: termite soldiers reduce the lethal impact of competitor cues on workers. Issue 4 (20th March 2017) - Tian, Li; Preisser, Evan L.; Haynes, Kenneth F.; Zhou, Xuguo
Abstract: While the impact of predator‐induced stress on prey has received considerable attention, there has been far less research into the effect of competitors. Cues from aggressive competitors should be particularly likely to evoke behavioral and/or physiological responses, since they may be indicative of both direct (interference) and indirect (exploitative) threats. The danger posed by such competitors, and the "fear" they evoke, should be reduced at lower competitor densities and by the presence of individual conspecifics specialized for defense. We assessed how Reticulitermes flavipes termite workers and soldiers were affected by cues from conspecific nestmates, conspecific non‐nestmates, and the heterospecific competitor R. virginicus . Competitor cues altered flavipes worker and soldier behavior, decreasing worker growth and increasing their mortality. The presence of flavipes soldiers largely ameliorated these negative impacts: adding even a single soldier (5% of flavipes individuals) decreased worker mortality by 50–80%. Although worker mortality increased with competitor density, increased soldier densities did not increase the benefit to workers. The small number of soldiers required to substantially alter cue‐mediated interactions suggests that this caste, in addition to providing direct defense, also occupies a "keystone role" by providing homeostatic feedback to workers functioning in stressful environments.